Problematika Problematika Minat Belajar pada Anak di Pesisir Pantai Kenjeran Kelurahan Sukolilo Baru Surabaya - Nisa, Hoirun; Listyaningsih (Kajian Moral dan Kewarganegaraan, 2024)
he interest in learning in children on the Kenjeran coast is still relatively low. Low interest in learning can be recognized through behavior such as not being serious about learning, getting bored quickly, trying to avoid learning activities and being lazy in learning. Children's interest in learning is very important so that children remain enthusiastic about getting an education. The purpose of this study was to describe (1) the form of problematic learning interest in children on the Kenjeran coast (2) the causal factors in the problematic learning interest in children on the Kenjeran coast. This study used a qualitative research method with a case study approach. Data were collected through observation, interviews, and documentation. The data were then analyzed using data analysis techniques by Miles Huberman which included data reduction, data presentation, and drawing conclusions. The results of the study showed that the form of problematic learning interest in children on the Kenjeran coast were 1) feelings of dislike for certain subjects 2) coastal children's interest in learning was still lacking 3) understanding of disliked subject matter was still lacking. Problems occur due to internal and external factors. Internal factors come from children who do not yet have an awareness of the need to learn which is still lacking because of a lack of motivation and high enthusiasm that has not been instilled in the child. While external factors come from the parental environment and friendship environment. Factors originating from the parental environment occur due to a lack of parental support and attention, the socio-economic limitations of parents so that children involve themselves in their parents' work, and the low level of parental education.